CHIR99021 Promotes hiPSC-Derived Cardiomyocyte Proliferation in Engineered 3D Microtissues - Hesselbarth, Ramona; Esser, Tilman; Roshanbinfar, Kaveh; Schrüfer, Stefan; Schubert, Dirk W.; Engel, Felix (Advanced Healthcare Materials, 2021)
Cardiac tissue engineering is a promising strategy to generate human cardiac tissues for modeling cardiac diseases, screening for therapeutic drugs, and repairing the injured heart. Yet, several issues remain to be resolved including the generation of tissues with high cardiomyocyte density. Here, it is shown that the integration of the glycogen synthase kinase-3β inhibitor CHIR99021 in collagen I hydrogels promotes proliferation of human-induced pluripotent stem cell-derived (hiPSC) cardiomyocytes post-fabrication improving contractility of and calcium flow in engineered 3D cardiac microtissues. CHIR99021 has no effect on the gelation kinetics or the mechanical properties of collagen I hydrogels. Analysis of cell density and proliferation based on Ki-67 staining indicates that integration of CHIR99021 together with external CHIR99021 stimulation increases hiPSC-cardiomyocyte number by ≈2-fold within 7 d post-fabrication. Analysis of the contractility of engineered cardiac tissues after another 3 d in the absence of external CHIR99021 shows that CHIR99021-induced hiPSC-cardiomyocyte proliferation results in synchronized calcium flow, rhythmic beating, increased speed of contraction and contraction amplitude, and reduced peak-to-peak time. The CHIR99021-stimulated engineered cardiac microtissues exhibit spontaneous rhythmic contractions for at least 35 d. Collectively, the data demonstrate the potential of induced cardiomyocyte proliferation to enhance engineered cardiac microtissues by increasing cardiomyocyte density.
CRIS-Team Scopus Importer:2021-09-17
Keywords: cardiomyocytes; CHIR99021; heart; hiPSC; proliferation; tissue engineering